The Fragility of Structural Legal Aid Implementation by the Legal Aid Institute of Padang: Institutional Challenges in Pursuing Structural Law Enforcement and Justice in West Sumatera - Rido Solihin Nasution; Syaflin Halim; Desi Asmaret; Romi Saputra (Green Publisher Indonesia, 2026)
Structural Legal Aid is an advocacy approach that not only focuses on individual defense but also seeks to address the structural roots of social and legal inequality. Within the sociocultural framework of West Sumatra, characterized by the Nagari system and customary communities, the Padang Legal Aid Institute adopts this approach in handling structural cases that reflect systemic injustice. This research aims to analyze the forms of Structural Legal Aid implementation by the Padang Legal Aid Institute and to identify the opportunities and challenges that affect its sustainability. Using a juridical-empirical method, this study is based on an inventory of data comprising the 2024 Annual Report of the Padang Legal Aid Institute, in-depth interviews with the Director and the Structural Legal Aid Division of the Padang Legal Aid Institute, as well as an examination of relevant legislation, legal literature, and scholarly journals. The research findings indicate that the implementation of Structural Legal Aid is carried out through an integration of litigation and non-litigation strategies that create an advocacy ecosystem bridging judicial processes and community movements. Opportunities for strengthening Structural Legal Aid arise from social capital, national advocacy networks, and the presence of paralegals at the nagari level, while the main obstacles include limited funding, the criminalization of human rights defenders, and weak policy support. This study contributes to the development of a contextual model of structural legal aid within Indonesia’s socio-legal framework and provides both conceptual and empirical insights for formulating community-based legal aid policies supported by the state